PEMANTAUAN PENGANGKUTAN LIMBAH BAHAN BERBAHAYA DAN BERACUN DARI PENGHASIL STUDI KASUS PUSKESMAS MUARA JAWA KABUPATEN KUTAI KARTANEGARA - mulya, widya -; Sari, Iin Pratama; Hartono , Ardiyanti Dina Sabrina (IDENTIFIKASI, 2023)
Puskesmas is a health service facility that organizes community and individual health efforts at the first level. The Muara Jawa Health Center in Kutai Kartanegara Regency produces Hazardous and Toxic Waste (B3) which is processed in collaboration with third parties, in the process of delivering B3 waste from producers to processing, B3 waste transportation services are required, where this transportation also requires collaboration with third parties. Throughout 2022, the average volume of medical waste at the Muara Jawa Health Center in Kutai Kartanegara Regency will reach 1 kg/day. The Muara Jawa Health Center, Kutai Kartanegara Regency, as a producer of B3 waste, must know the completeness of the documents and the safety of the vehicle and the driving of the B3 waste transporters who are invited to cooperate, this is to avoid incidents, one of which is the illegal transport of B3 waste. The aim of the study was to find out the results of monitoring the transport of Hazardous and Toxic Waste (B3) from producers at the Muara Jawa Health Center, Kutai Kartanegara Regency. This research was conducted by observing the completeness and safety of transporting B3 waste, interviewing employees of environmental health at the Muara Jawa Community Health Center, Kutai Kartanegara Regency. Based on the results of observations and interviews, the completeness and safety of transporting B3 waste refers to the Regulation of the Minister of Environment and Forestry Number 6 of 2021 concerning Procedures and Requirements for the Management of Hazardous and Toxic Waste , obtaining an assessment result of 94.11% according to conditions lacking in the festronic section for transporting B3 waste which still uses manifest. Keywords: Monitoring, Transportation, Hazardous and Toxic Waste, Producer.